Citizen participation in public policy. The hearing in Argentina: The case of the “Gas Audience” (2016) - Eberhardt, María Laura (Derecho Público Iberoamericano, 2017)
The hearing is a citizen participation mechanism that enables individuals, individually or on behalf of a group, to expose to the authorities their opinion or proposal regarding a public policy that affects them. The participation is consultative or informative but not decisive, since its results are not binding. In Argentina, this instrument was incorporated into several public service legislations and regulated by decree of the national executive in 2003. It is a mechanism whose application in the country was reduced to cases of compulsory convocation by law, a purely formal application, and without greater intervention of the citizens nor general repercussion. However, in 2016 the gas hearing had a broad social, political and media impact. Analyzing the institutional design of this tool as well as this application case, will allow to identify its advantages and limitations for citizen participation.